Late onset palmar angiokeratoma circumscriptum: An unusual presentation - Saurabh R Jindal; Pallavi Chalvade; H R Jerajani (Wolters Kluwer Medknow Publications, 2014)
Angiokeratomas (AK) are a group of capillary vascular malformations encompassing several unrelated conditions, predominantly seen on the lower extremities. AK can be classified into localized and diffuse forms. The diffuse forms comprise Fabry's disease, which is the result of α-galactosidase deficiency. The cutaneous AK includes the Mibelli type, the Fordyce type, angiokeratoma circumscriptum (AC), and 'solitary and multiple papular angiokeratoma'. We describe a case of AC with unusual features including late onset and palmar affection. Amongst the possible therapeutic options, cryotherapy was considered. However, the patient was lost to follow up.